Extraction and characterization of cellulose nanofibers from rice husk: Potential for electrospun PVA/CNF mat composites (Kuwait Journal of Science)
The current study examined the viability of synthesizing cellulose nanofibers (CNFs) from rice husk using acid hydrolysis 10 % HCl. The PVA polymer solution was enhanced with Triton x-100 as a surfactant and different amounts of CNF were introduced before the electrospinning procedure. The CNF extracted in this study had a diameter of 9.6 nm. It exhibited elongated, fibrous formations like a web, with a crystallinity level of 70 %. The negative charge from the CNF was introduced to augment the conductivity and viscosity of the rotating fluid. The Fourier transform infrared (FTIR) studies validated the interaction between PVA and CNFs throughout their mixing process. The use of CNF enhanced the thermal stability of the PVA nanofibrous composite. The PVA/CNF nanofibrous composite displayed smooth surfaces and potential for diverse medical applications, food packaging, and water purification. © 2025 The Authors